Efektivitas Media Audio Visual Berbasis Aplikasi Spinning Wheel untuk Meningkatkan Hasil Belajar Maharoh Kalam Kelas VIII MTs Ma’murotul Husna - Ainiyah, Wafi I’anatul; Sholihuddin, Ahmad (Al-Wasil, 2025)
This study aims to determine how the application and effectiveness of audio-visual media in improving the learning outcomes of maharoh kalam of class VIII students of MTs Ma'murotul Husna, by utilizing Audio-Visual media based on the Spinning-Wheel Application. The research method used in this study is a quantitative approach with a quantitative experimental research type. While the research design used is Pre-Experimental One Group Pretest-Posttest Design. In this case, the independent variable is audio-visual media based on the Spinning Wheel application and the dependent variable is the learning outcomes of maharoh kalam. Based on the results of the calculation of the difference test using paired sample t-test between the pre-test and post-test values. The results of the paired sample t-test in this study were 0.000 or with a significance level of 0.000 <0.005 so that it can be concluded that there is a significant difference during the pre-test and post-test of the experiment. These results indicate that the use of audio-visual media based on the Spinning Wheel application is effective in improving the learning outcomes of maharoh kalam class VIII MTs Ma'murotul Husna. So it can be concluded that: 1) the application of audio-visual media based on the spinning wheel application can facilitate an educator and help students in the learning process, 2) audio-visual media based on the Spinning Wheel application is effective in improving the learning outcomes of maharoh kalam of class VIII students of MTs Ma'murotul Husna. So, this shows that the application of audio-visual media based on the Spinning Wheel application is effective in significantly improving the learning outcomes of maharoh kalam in Arabic.